Effect of RH on creep of concrete – some studies relevant to Indian conditions - Balu, Arun; Rao, K. Balaji; Anoop, M.B.; Kamatchi, P.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Relative humidity (RH) and temperature are two major environmental factors affecting the creep of concrete. The provisions in IS 456-2000 for determining the creep deflections of flexural members do not explicitly take into consideration the effect RH and temperature, and, using IS 456-2000 a designer will obtain a single value for creep deflection for the flexural member (irrespective of the exposure condition). Investigations have been taken up at CSIR-SERC to study the effects of RH and temperature prevailing in different parts of the country on creep of concrete. The information regarding the RH and temperature in 42 cities in the country, ranging over periods of 5 years to 30 years, is obtained from authentic sources. Based on the data, first-cut RH- and temperature- maps of India are prepared. It is well known that the effect of RH on creep of concrete is more than the effect of temperature for most of the structures1. Hence, the effect of RH on creep of concrete is studied by comparing the creep deflections of a reinforced concrete beam, considering the beam to be exposed to the RH environments of the 42 cities considered. Both ACI 209-92 and B3 creep models are considered in the study. The results obtained show that there are large variations in the creep deflections obtained for the beam when it is exposed to different RH environments. This suggests that there is a need to explicitly consider the effect of RH on creep of concrete in IS 456-2000.